Simultaneous determination of Cu, Pb, Cd, Ni, Co and Zn in bioethanol fuel by adsorptive stripping voltammetry and multivariate linear regression - Silva Do Nascimento, Danielle (2014)
In this work it is proposed the one-voltammogram simultaneous determination of Cu(II), Pb(II), Cd(II),Ni(II), Co(II), and Zn(II) at ppb and sub-ppb levels in bioethanol fuel samples by adsorptive stripping voltammetry.Mixed ligands were employed providing stripping peaks for all analytes at the same voltammetricscan under optimized conditions. To perform the determination, multivariate linear regressionaided by successive projections algorithm (SPA?MLR) was evaluated. The voltammograms were preprocessedwith the asymmetric least squares (AsLS) baseline correction algorithm and the icoshift peak alignmenttool. An excellent analytical performance was obtained, despite the inherent complexity of thesimultaneous determination, with average apparent recovery = 96% ± 16%, and better prediction resultsin comparison with the benchmark method of partial least squares (PLS)